PROVERB: AN ANALYSIS OF TRANSLATION FROM PASHTO TO ENGLISH - Mujtaba Khan; Sumaira Rauf; Sumbal Imran (International Journal of Contemporary Issues in Social Sciences, 2023)
The translation of proverbs has always been a challenging area, and it is an important part of cultural heritage due to its connection with folklore. As a result, translators often encounter difficulties at the lexical, syntactical, and cultural levels. To address this issue, the current study aimed to analyze Pashtu proverbs and their English equivalents, i.e., their translated versions. The proverb books Matalona and Da Matalono kitab by Akbar S Ahmad was used as a source of data, which contains both the original proverbs and their translations. The Gorjian model, which involves literal translation, near equivalence, and exact equivalence procedures, was utilized to analyze the proverbs. The proverbs were examined to determine whether they were translated literally or according to their meaning. The findings suggest that there is a mix of both literal and sense translations, and the level of equivalence varies among different versions.